Potraits of Women in Republika Online News: a Corpus Linguistic Analysis - Fatim, Al Lastu Nurul; Arifa, Zakiyah; Basid, Abdul; Lestari, Sri Wahyuni (Balai Bahasa Kalimantan Tengah, 2024)
The news media's depiction of women tends to produce various perceptions that are negative, positive, or neutral. That statement is displayed based on language and word sorting in expressing each event. This study aims to reveal the portrait of women in Republika online news media based on corpus linguistic analysis. This research data is in the form of text from Republika online news media. This research uses descriptive quantitative and qualitative approaches. News texts formatted and converted to the UTF-8 text encoding standard are then analyzed with AntConc software to reveal linguistic features. The results show the analysis of three linguistic features: word frequency, collocation, and concordance. First, the frequency of occurrence of the word significantly displays fairly common news with narrative writing that prioritizes the position of women as the subject. Secondly, collocation analysis tends to collocate with nouns representing actions, events, or states. Third, concordance analysis tends to have a positive conclusion, preserving crucial issues in reality.